Comparative Analysis of the Host Response in a Rat Model of Deep-Partial and Full-Thickness Burn Wounds With Pseudomonas aeruginosa Infection - Weaver, Alan J.; Brandenburg, Kenneth S.; Smith, Brian W.; Leung, Kai P. (Frontiers in Cellular and Infection Microbiology, 2020)
Burn wound injury affects soldiers and civilians alike, often resulting in a dynamic, but un-orchestrated, host response that can lead to infection, scarring, and potentially death. To mitigate these factors, it is important to have a clinically relevant model of burn wound infection that can be utilized for advancing burn wound treatments. Our previous reports have demonstrated the ability of Pseudomonas aeruginosa to generate a biofilm infection within a modified Walker-Mason rat burn model of deep-partial (DPT) and full-thickness (FT) burn wounds (10% total body surface area) in male Sprague-Dawley rats (350-450 g). Here, we further define this model with respect to the host response when challenged with P. aeruginosa infection between the two burn types. Following burn injury and immediate surface exposure to P. aeruginosa, inflammation at the local and systemic levels were monitored for an eleven day period. Compared to burn-only groups, infection with P. aeruginosa further promoted local inflammation in both DPT and FT burn wounds, which was evident by enhanced cellular influx (including neutrophils and monocytes), increased levels of several pro-inflammatory cytokines (IL-1β, IL-6, GRO/KC, and MIP-1α), and reduced IL-10. Systemically, only minor changes were seen in circulating white blood cells and cytokines; however, increases in high mobility group box-1 (HMGB-1) and hyaluronan, as well as decreases in fibronectin were noted particularly in FT burns. Compared to the burn-only group, P. aeruginosa infection resulted in sustained and/or higher levels of HMGB-1 and hyaluronan. Combined with our previous work that defined the burn depth and development of P. aeruginosa biofilms within the wound, this study further establishes this model by defining the host response to the burn and biofilm-infection. Furthermore, this characterization shows several similarities to what is clinically seen and establishes this model for future use in the development and testing of novel therapeutics for burn wound treatment at home and on the battlefield.